(5x+2)(2x-5)=0

Simple and best practice solution for (5x+2)(2x-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+2)(2x-5)=0 equation:


Simplifying
(5x + 2)(2x + -5) = 0

Reorder the terms:
(2 + 5x)(2x + -5) = 0

Reorder the terms:
(2 + 5x)(-5 + 2x) = 0

Multiply (2 + 5x) * (-5 + 2x)
(2(-5 + 2x) + 5x * (-5 + 2x)) = 0
((-5 * 2 + 2x * 2) + 5x * (-5 + 2x)) = 0
((-10 + 4x) + 5x * (-5 + 2x)) = 0
(-10 + 4x + (-5 * 5x + 2x * 5x)) = 0
(-10 + 4x + (-25x + 10x2)) = 0

Combine like terms: 4x + -25x = -21x
(-10 + -21x + 10x2) = 0

Solving
-10 + -21x + 10x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-2 + -5x)(5 + -2x) = 0

Subproblem 1

Set the factor '(-2 + -5x)' equal to zero and attempt to solve: Simplifying -2 + -5x = 0 Solving -2 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 0 + 2 -5x = 0 + 2 Combine like terms: 0 + 2 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4

Subproblem 2

Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5

Solution

x = {-0.4, 2.5}

See similar equations:

| -(-9-4y)= | | g-1=5-1-9 | | -1(p+6)= | | 36y^2-1=15 | | 3.7q-1.9-3.4q=-0.7q-1.9 | | (1-11j)4= | | 3.7q-1.9q-3.4q=-0.7q-1.9 | | 7(11-n)= | | 0.3q-1.9=-0.7q-1.9 | | 12(4-8p)= | | 7+2(a-3)= -9 | | 17(2b+3)= | | 5m+5=7m-7 | | (6y-3)5= | | 3x^3-13x^2+16=0 | | (2h-4)11= | | 3t^2+4t+1=0 | | 3(2+w)= | | g(-1)=5(-1)-9 | | 4x-6x-4=0 | | 4x(x+2)-x(3+4)=2x+18 | | 7(z-4)= | | 4x^2+21x+22=-4x+4 | | 5(x-2)=8#-3 | | 12x-41+5x+5y= | | Y=Ax-Fx-C | | z^6-z^3-2=0 | | (12x-8)+3(2x-4)= | | 10x+3=3(2x+1)-x+8 | | -x+3+9x=-2+3x+10 | | -11c=89 | | 5=-3(x+2)-4 |

Equations solver categories